Correlation analysis of seed yield and its component traits in Sesame (Sesamum indicum L.): Correlation analysis of seed yield and its component traits in Sesame (Sesamum indicum L.) - ROHIT; SUBHASH CHANDER; ROHIT KUMAR (Journal of Oilseeds Research, 2023)
Oilseed crops are high-value agricultural commodity for use in edible oil products. Sesame is an In the present study, fifty genotypes were evaluated to assessthe association among seed yield and its component traits in Sesame, during kharif 2022, in randomized block design with three replications. Significant differences were observed for all the characters. Seed yield per plant showed a significant and positive correlationwith plant height, number of capsules per plant and 1000-seeds weight at both genotypic and phenotypiclevel indicated that these were main contributors to the seed yield.